Experimental Assessment of the Effect of Acute Radiation on Immune System Indicators and the Efficiency of Biocorrection (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The aim of the study was to determine the effect of acute radiation on the immune status of experimental animals and to demonstrate the degree of influence of biocorrection on this process. It was found that the relative and absolute indicators of immune system cells in male white rats that received and did not receive acute radiation were different. This was observed in the total number of lymphocytes, the number of CD3+-, CD4+- and CD8+-cells. A decrease in IRI in the main group by 2.01 times was recognized as the main sign of the development of secondary immunodeficiency. It was found that there were no obvious changes in CD20+-cells, CD16+-cells significantly increased by 1.35 times in the main group of laboratory animals, and CD95+-cells significantly decreased by 1.51 times. In the biocorrected group, the immune system failure was not relatively deep, it was proved that the used biopreparation has an immunostimulating effect, its use reduces the negative effect of acute radiation on the indicators of immune system cells.